Does Gender Diversity Moderate The Relationship Between Social Responsibility to Corporate Performance and Reputation Sharia Companies? - Devy, Happy Sista; Pratama, Versiandika Yudha; Fakir, Fatima Zahra; Ariqotul'ula, Nada Nuzulul (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
Purpose: The purpose of this study is to analyze the effect of corporate social responsibility (CSR) on firm value and corporate reputation with gender diversity as a moderating variable in Indonesia and Malaysia.Design/methodology: The method used is a verification method using E-views tools using normality test, model test, regression test and MRA test for moderation testing. The population in this study were included in IDX-MES BUMN 17 and companies included in FTFBHMS. Determination of the sample using purposive sampling, 12 companies in Indonesia and 10 companies in Malaysia were obtained.Findings: The results showed that in sharia companies in Indonesia CSR has a positive and significant effect on firm value and corporate reputation. However, gender diversity is not able to moderate the effect of CSR on firm value and corporate reputation. Different results in the research sample of Islamic companies in Malaysia show a significant positive effect on CSR on firm value and corporate reputation but gender diversity is able to moderate the effect of CSR on firm value and corporate reputation. The greater the gender diversity within the company in important positions can increase the effect of CSR on firm value and corporate reputation. The better companies disclose their CSR, the better the company's reputation will be and can increase the company's value.Practical implications: This study provides evidence that CSR disclosure can improve firm performance and reputation. The findings also provide insight to companies and investors that gender diversity is important because it can increase the influence between CSR and company performance and reputation. The weak role of female directors may make the effect insignificant.Originality/Value: This research extends the study of corporate performance and reputation, and expands its influence with the moderating variable gender diversity. This study explains the link with stakeholder theory and legitimacy theory on performance, corporate reputation, CSR and gender diversity